Caesio xanthalytos, a new species of fusilier (Perciformes: Caesionidae) from the Western Indian Ocean, with records of range extensions for several species of Caesionidae - Holleman, Wouter; Connell, Allan D.; Carpenter, Kent E. (Zootaxa, 2013)
Caesio xanthalytos, a new species of fusilier, closely related to Caesio caerulaurea Lacepède 1801, is described from several specimens from various localities on the east coast of Africa, and from southern Madagascar. While very similar in colour pattern to C. caerulaurea, its lateral line lies within a dominant, composite yellow stripe, whereas in C. caurulaurea the lateral line lies immediately below the yellow stripe. The two species also differ in the number of lateral-line scales, the modal number of pectoral-fin rays, in the form of the nuchal scale patch, and genetically. The new species has been observed to school with C. caerulaurea and with C. varilineata Carpenter 1987. The ranges of several species of Caesio and Pterocaesio and of Dipterygonotus balteatus and Gymnocaesio gymnoptera are extended to localities on the South African east coast.